Search title Procedures for transferring documents from paper to digital format: An analytical study - Ayman Bassiouny (The International Journal of Informatics, Media and Communication Technology, 2020)
Dealing with huge amounts of information in traditional ways has become difficult in a particular place, even if the complexity and overlapping of interests between the different institutions between them, as well as between these institutions and the members of the community that they serve, has necessitated dealing with more than one customer at the same time and with the same documents sometimes and this is not provided by the work environment Paper, the dealing in the paper environment does not exceed two at one time as it is prone to loss or damage, and from here emerged to us another different environment which is the digital environment for dealing with official records and files and archiving them electronically to achieve more effectiveness in dealing with them. This research aims to shed light on the importance of the digital transformation in institutional work, the procedures followed and the various stages of completing the transformation process from paper to digital.